Rising synchrony controls western North American ecosystems. (10th April 2018) - Black, Bryan A.; van der Sleen, Peter; Di Lorenzo, Emanuele; Griffin, Daniel; Sydeman, William J.; Dunham, Jason B.; Rykaczewski, Ryan R.; García‐Reyes, Marisol; Safeeq, Mohammad; Arismendi, Ivan; Bograd, Steven J.
Abstract: Along the western margin of North America, the winter expression of the North Pacific High (NPH) strongly influences interannual variability in coastal upwelling, storm track position, precipitation, and river discharge. Coherence among these factors induces covariance among physical and biological processes across adjacent marine and terrestrial ecosystems. Here, we show that over the past century the degree and spatial extent of this covariance (synchrony) has substantially increased, and is coincident with rising variance in the winter NPH. Furthermore, centuries‐long blue oak ( Quercus douglasii ) growth chronologies sensitive to the winter NPH provide robust evidence that modern levels of synchrony are among the highest observed in the context of the last 250 years. These trends may ultimately be linked to changing impacts of the El Niño Southern Oscillation on midlatitude ecosystems of North America. Such a rise in synchrony may destabilize ecosystems, expose populations to higher risks of extinction, and is thus a concern given the broad biological relevance of winter climate to biological systems. Abstract : Along the western margin of North America, the winter North Pacific High (NPH) induces covariance (synchrony) within and across adjacent marine and terrestrial ecosystems, as reflected in such processes as coastal upwelling, precipitation, river discharge, and blue oak ( Quercus douglasii ) growth chronologies. Over the past century the degree and spatial extent of this synchrony has substantially increased, coincident with rising variance in the winter NPH. These trends may be linked to changing impacts of the El Niño Southern Oscillation and are of concern given the potential for synchrony to destabilize ecosystems and expose populations to higher risks of extinction.